Utilização de nanosílica como aditivo estendedor para pastas cimentantes de baixa densidade destinadas à cimentação de poços petrolíferos - Ribeiro, Danilo Brasil (2012)
Cementing operations are conducted at different times of the well s life and they have high importance, because the functions are fundamental to keep good properties during a long life of the well, such as, maintain the mechanical stability of the well, to promote the isolation hydraulic and support the tubing. In some situations, the rocky zones have low fractures pressures and require the use of lightweight slurries to prevent the hydrostatic pressure in the formation is greater than the pressure of fracture. There are three ways to reduce the density of cement slurries: exterders water additives, microspheres and foamed slurries. The most used extender water additive is sodium bentonite, which is a clay with a good capacity of water absorption and expansion of its volume, the main disadvantage of this additive is the reduction of the strength. Currently, the use of nanoscale particles has received special attention, mainly because they get new functionalities. Following this trend, this paper aims to use a colloidal solution of nano-silica as an exterders water additives for use in oil wells. Slurries were designed with fixed 13lb/gal density and concentration of nano silica 0.1 gpc; 0.4 gpc; 0.7 and 1gpc, the influence of nano-silica was studied at these levels in isolation and combined varying concentrations of CaCl2,. Tests including rheology, stability, strength, thickening time, porosity and permeability. Besides the API tests, microstructural characterizations were performed after 28 days of the slurries, X-ray diffraction (XRD) and scanning electron microscopy (SEM)